Incidence and survival of end-stage kidney disease due to polycystic kidney disease in Australia and New Zealand (1963–2014). Issue 1 (December 2017) - Fernando, Mangalee; Dent, Hannah; McDonald, Stephen; Rangan, Gopala
Abstract Background The aim of this study was to determine whether the incidence and survival of patients with end-stage kidney disease (ESKD) due to polycystic kidney disease (PKD) has changed in Australia and New Zealand. Methods Data for all PKD patients who developed ESKD and commenced renal replacement therapy (RRT) was assessed using the Australia and New Zealand Dialysis and Transplant Registry from 1963 to 2014. Results A total 4678 patients with ESKD due to PKD received RRT during the study period. The incidence rate of ESKD (per million population per year) due to PKD rose by 3.2-fold (1970–2010), but the percentage increase between each decade decreased (54.4, 43.8, 25.6 and 6.57%). The median age of onset of new patients developing ESKD has been stable since 1990. Haemodialysis was the most common initial mode of RRT (between 62 and 76% of patients) whereas 24–29% received peritoneal dialysis. The 5-year survival rate of PKD patients on RRT (censored for transplantation and adjusted for age) improved from 26 to 84%, with the percentage increase between each successive time period being 123, 7, 21, 19 and 7.4%. The percentage of deaths on RRT due to cerebrovascular disease declined from 15 to 6%. Conclusions The incidence and age of onset of ESKD due to PKD has remained unchanged in the modern era though patient survival on RRT has continued to improve. These data suggest that the development and implementation of disease-specific treatments prior to RRT is needed to effectively diminish the incidence of ESKD due to PKD.